Tren Baru dalam Pengelolaan Kelas Tinjauan Blibliografi Terhadap Metode Pengajaran Aktif dan Memaksimalkan Keterlibatan Siswa melalui Perspektif Psikologis - Rahmatul Hayati; Wahyu Prima (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Effective classroom management is a key factor in enhancing student learning quality. In recent years, educational strategies have evolved significantly, marked by the increased adoption of active teaching methods that emphasize students' roles as active participants. This article conducts an in-depth bibliometric review using primary databases such as Scopus and Web of Science, focusing on literature published over the past five years. The review indicates that despite a rise in publications, further research is still required to support the integration of these methods into the curriculum. The two most cited articles offer implementable strategies adaptable for teachers across various learning contexts, whereas research with a local focus is frequently overlooked. This article highlights the importance of active teaching strategies examined through a psychological perspective in enhancing learning dynamics and outcomes. Through this analysis, the article underscores the need for innovation in teaching strategies to adapt to modern educational demands and offers practical recommendations for educational practitioners.